MAGMATIC SOURCES OF THE EVOLVING CONTINENTAL TECTONOSPHERE IN INDIA: GENERATION OF ALKALINE IGNEOUS COMPLEXES WITH CARBONATITES IN THE SAMALPATTI (SOUTHERN INDIA) AND AMBA DONGAR (WESTERN INDIA) MASSIFS - S. V. Rasskazov; T. A. Yasnygina; K. R. Hari; I. S. Chuvashova; E. V. Saranina (Геодинамика и тектонофизика)
Neoproterozoic Samalpatti and Cretaceous-Paleogene Amba Dongar massifs are considered to evaluate the change of sources of carbonatite magmatism in evolving tectonosphere of India. The inherited character of Ba and Sr distribution components is traced in heterogeneous carbonatites of India, whereas the independent trends in Ba and Sr enrichment are traced in carbonatites of North Asia. It is inferred that in the process of activity in the tectonosphere of the Indian subcontinent ~800 Ma ago, carbonatite melts were generated in the mantle whose photolith has an age of 4.26 Ga. This protomantle reservoir was remarkably different from the primordial mantle reservoir in the solidified magma ocean in terms of low initial μ and high initial Nd isotope ratio. After the Indian subcontinent had separated from Gondwana 130–100 Ma ago and began to join Asia ~66 Ma ago, ELMU source was activiated in the tectonosphere. The Amba Dongar carbonatites might have been derived from the 4.40 Ga mantle protoliths. Silicate melts of the Deccan LIP were simultaneously generated from the protoliths with Pb-Pb age of ~2 Ga.